Use of ladle slag for CO₂ sequestration and zinc immobilization - Xu, Bo (2024)
Environmental pollution, waste management, and greenhouse gas emissions pose significant challenges to global sustainable development. To address these challenges, this study introduces an innovative approach by reusing an industrial waste, ladle slag (LS), and greenhouse gas, CO2, for fast immobilization of zinc. In this study, specimens were prepared by mixing LS with zinc nitrate with initial concentrations of 0–25,000 mg/kg and then subjected to conventional and CO2 curing. Leaching test and chemical analysis tests were also conducted. The results showed that LS with CO2 requires only 112 hours to achieve around 2–3 times lower leaching concentrations than that of conventional curing for 28 days, being around 1–2 orders of magnitude lower than that without CO2 and conventional curing. Simultaneously, CO2 up to 13.5 % of LS mass was also sequestered. This approach provides a triple benefit by simultaneously immobilizing zinc, mitigating LS landfilling, and capturing CO2.